Inclusive quarkonium production at forward rapidity in pp collisions at √s = 8 TeV - Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Alam, S.N.; Aleksandrov, D.; et al. (Springer New York LLC, 2016)
We report on the inclusive production cross sections of J/ψ, ψ(2S), ϒ(1S), ϒ(2S) and ϒ(3S), measured at forward rapidity with the ALICE detector in pp collisions at a center-of-mass energy √s = 8 TeV. The analysis is based on data collected at the LHC and corresponds to an integrated luminosity of 1.23 pb−1. Quarkonia are reconstructed in the dimuon-decay channel. The differential production cross sections are measured as a function of the transverse momentum pT and rapidity y, over the pT ranges 0 < pT < 20 GeV/c for J/ψ, 0 < pT < 12 GeV/c for all other resonances, and for 2.5 < y < 4. The cross sections, integrated over pT and y, and assuming unpolarized quarkonia, are σJ/ψ = 8.98 ± 0.04 ± 0.82 µb, σψ(2S) = 1.23 ± 0.08 ± 0.22 µb, σϒ(1S) = 71 ± 6 ± 7 nb, σϒ(2S) = 26 ± 5 ± 4 nb and σϒ(3S) = 9 ± 4 ± 1 nb, where the first uncertainty is statistical and the second one is systematic. These values agree, within at most 1.4σ, with measurements performed by the LHCb collaboration in the same rapidity range.
Keywords: Physics; Rapidity; Quarkonium; Particle physics; Production (economics); Sigma; Luminosity; Energy (signal processing); Large Hadron Collider; Nuclear physics; Quantum chromodynamics; https://purl.org/pe-repo/ocde/ford#1.03.04